(3eYLRI aj GdVaI GdZQHjI (B/s - (3Ndjd, YeGO GdOjf,s 1939- ((3OeTb ;s (3HjQhJ (B:s (3OGQ GHf cKjQ,s, 2010)
(3aj gPG GdcJGH eSQMjGJ ESdGejI PGJ aUd hGMO, JYGdL GKfJGf efgG hgeG (B: "(3eYLRI aj GdVaI GdZQHjI(B" (3h(B"(3UQNI YfO GdeSLO GdCbUi(B" (3MdbJjf eJhgLJjf ef edMeI GdYed GdaOGFj aj GdSGMI GdadSWjfjI, YHQ HOGjGJg GdChdi(B. (3HjfeG JYGdL (B((3GdHdGZ Qbe (B7) (3OQGeG GdUQGY GdPj dG jfJgj Hjf GdEjeGf hGdWGZhJ, hHjf GdJhMjO hGdhKfjI; CeG (B((3TjA Yf GdehJ(B) (3aEfgG JJYGed eY hGbYI GdehJ, hJOjQ GdcGejQG, YHQ HGNQI JLJGR GdHMQ GdeJhSW, hJhTc Ydi GdZQb(B... (3Ydi ehGba eJZGjQI, heJfGbVI, ERGA gPg GdhGbYI GdJj jecf Cf JSJeO efgG GdcKjQ, HOdG ef GdjCS hGdGSJSdGe hCeG (B((3CcGOjejhf(B) (3agj chejOjG JYQV HCSdhH SGNQ dLedI ef GdeeGQSGJ GdJj JOhQ aj HYV GdLGeYGJ GdYQHjI, MjK jUjQ (B((3GddbH GdYdej(B) (3h(B((3GdeXGgQ(B)(3, hRjGOI GdeONhdGJ GdeGdjI, GdCgOGa GdJj jJbGJd YdjgG GdCcGOjejhf, hMjK JSMH Edi GdXd eWGdH GdEHOGY aj GdYedjI GdJOQjSjI Ch GdHMK GdYdej(B.s
(3GdeSQMjI GdYQHjI(B.s
Keywords: (3GdeSQMjGJ GdYQHjI GdOjfjIs -- (3GdYQGbs -- (3bQf (B20s; (3GdVaI GdZQHjI (B((3adSWjf(B)s -- (3eSQMjGJs